2015
DOI: 10.1016/j.jss.2015.04.074
|View full text |Cite
|
Sign up to set email alerts
|

One-year postoperative resource utilization in sarcopenic patients

Abstract: Introduction It is well established that sarcopenic patients are at higher risk of postoperative complications and short-term healthcare utilization. Less well understood is how these patients fare over the long-term after surviving the immediate postoperative period. We explored costs over the first postoperative year among sarcopenic patients. Methods We identified 1,279 patients in the Michigan Surgical Quality Collaborative database who underwent inpatient elective surgery at a single institution from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…Further, sarcopenia has been shown to influence drug pharmacokinetics (28) and can lead to increased drug toxicities (29). Finally, sarcopenic patients have been found to accrue increased costs in the first 6 months after a surgical procedure (30). However, little work has been done to date in clarifying the impact of sarcopenia in an older adult trauma population.…”
Section: Discussionmentioning
confidence: 99%
“…Further, sarcopenia has been shown to influence drug pharmacokinetics (28) and can lead to increased drug toxicities (29). Finally, sarcopenic patients have been found to accrue increased costs in the first 6 months after a surgical procedure (30). However, little work has been done to date in clarifying the impact of sarcopenia in an older adult trauma population.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Emerging data suggest that frailty and sarcopenia affect survival after LT independent of recipient and donor factors. Using analytic morphomics, we and others have shown that body composition, especially the dorsal muscle group (DMG) area (psoas and paraspinal muscles), predicts postoperative complications (5)(6)(7) and survival after LT independent of MELD score. (6,(8)(9)(10)(11)(12) Analytic morphomics is a novel approach that uses high throughput semiautomated image-processing techniques to assess body composition, such as body dimensions, visceral fat (VF), and muscle mass, and to link it to clinical outcomes.…”
mentioning
confidence: 99%
“…After the process of selection based on abstract and title and after on the full-text article review ( Fig. 1), we finally included 14 studies assessing the difference in health care costs between individuals with or without sarcopenia [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Sixteen studies were rejected because of duplicate (n = 2) [11,20], wrong outcomes (n = 13) [24][25][26][27][28][29][30][31][32][33][34][35][36] or wrong exposure factor (n = 1) [38].…”
Section: Literature Searchmentioning
confidence: 99%
“…A complete presentation of the characteristics and design of the 14 included studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23] is accessible in Table 3. All studies, specifically regarding their analysis of sarcopenia-related costs, followed a cross-sectional design and was comprised of 50 to 1593 participants.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation